Expression of Calcification and Extracellular Matrix Genes in the Cardiovascular System of the Healthy Domestic Sheep (Ovis aries) - Tsang, Hiu-Gwen; Clark, Emily L.; Markby, Greg R.; Bush, Stephen J.; Hume, David A.; Corcoran, Brendan M.; MacRae, Vicky E.; Summers, Kim M. (Frontiers in Genetics, 2020)
The maintenance of a healthy cardiovascular system requires expression of genes that contribute to essential biological activities and repression of those that are associated with functions likely to be detrimental to cardiovascular homeostasis. Vascular calcification is a major disruption to cardiovascular homeostasis, where tissues of the cardiovascular system undergo ectopic calcification and consequent dysfunction, but little is known about the expression of calcification genes in the healthy cardiovascular system. Large animal models are of increasing importance in cardiovascular disease research as they demonstrate more similar cardiovascular features (in terms of anatomy, physiology and size) to humans than do rodent species. We used RNA sequencing results from the sheep, which has been utilised extensively to examine calcification of prosthetic cardiac valves, to explore the transcriptome of the heart and cardiac valves in this large animal, in particular looking at expression of calcification and extracellular matrix genes. We then examined genes implicated in the process of vascular calcification in a wide array of cardiovascular tissues and across multiple developmental stages, using RT-qPCR. Our results demonstrate that there is a balance between genes that promote and those that suppress mineralisation during development and across cardiovascular tissues. We show extensive expression of genes encoding proteins involved in formation and maintenance of the extracellular matrix in cardiovascular tissues, and high expression of haematopoietic genes in the cardiac valves. Our analysis will support future research into the functions of implicated genes in the development of valve calcification, and increase the utility of the sheep as a large animal model for understanding ectopic calcification in cardiovascular disease. This study provides a foundation to explore the transcriptome of the developing cardiovascular system and is a valuable resource for the fields of mammalian genomics and cardiovascular research.